94 Effect of dietary with probiotics complex (B. subtilis and B. licheniformis) supplementation on reproduction performance, nutrient digestibility, blood profile, fecal noxius gas emission, and fecal microflora in lactation sows and sucking piglets. (10th April 2018) - Hu, J; Lee, D J; Kim, Y M; Cheng, L; Kim, I H
Abstract: The objective of this study was to evaluate the effects of dietary with probiotics complex ( B. subtilis and B. licheniformis ) supplementation on reproduction performance, nutrient digestibility, blood profile, fecal noxius gas emission, and fecal microflora in lactation sows and sucking piglets. A total of 24 multiparous sows (Landrace × Yorkshire) and their litters were used in a 28-day experiment. On day 111 of gestation, sows were randomly allotted to three dietary treatments with 8 replicate pens per treatments based on parity number according to a randomized complete design. The dietary treatments were as follows : 1) CON (Basal diet), 2) TRT1 (CON + 0.1% probiotics complex), 3) TRT2 (Basal diet + 0.2% probiotics complex). All data were analyzed using the MIXED procedure for a randomized complete block disign. The significance level was set at p < 0.05. The results showed that sows fed the TRT2 diets had higher (quadratic, P = 0.047) stillbirth head compared with CON group. Sows fed the TRT2 diet linearly increased the body weight at 3 wk and finish phase (p = 0.0373, p = 0.0104, respectively), and average daily gain in suckling pigs at 2 wk, 3 wk, 4 wk and overall compared with CON group (p = 0.0200, p = 0.0054, p = 0.0035 and p = 0.0154, respectively). The digestibility of dry matter in sow fed the TRT2 diets were higher (liner, p = 0.0034) compared with those fed the CON diet during whole experiment. At weaning, sows fed TRT2 diets had decreased NH3 (linear, P = 0.0454) as compared with CON group. Sows fed the TRT2 diets had reduced (quadratic, P = 0.0414; linear, P = 0.0002) E. coli population at weaning, but before farrowing. In conclusion, 0.2% probiotics complex supplementation in sow diets could improve the stillbirth, the ATTD of dry matter and energy, as well as decrease the NH3 and total mercaptan, E. coli at weaning phase. In addition, suckling piglets' body weight and average daily gain had increased by 0.2% probiotics complex supplementation.